Isoductile strengths and strength reduction factors of elasto-plastic SDOF systems subjected to simple waveforms. - Cuesta, Isabel (Earthquake engineering & structural dynamics.)
The inelastic response of elasto plastic SDOF oscillators subjected to 24 simple waveforms was studied. The waveforms contain linear, quadratic, sinusoidal, and triangular acceleration components that repeat for not more than several cycles. Similarities and differences in oscillator response characteristics are presented, organized by a characteristic period. The strengths and corresponding strength reduction factors required for constant ductility responses are discussed. Response data are compared with expectations based on the concepts of equal energy, equal displacement, and preservation of force. Limitations on the applicability of the equal energy concept are identified.